RELATIONSHIP COUNSELING SERVICES GROUP WITH ISLAMIC RELIGIOUS EDUCATION ACHIEVEMENT - Ikhwati Wahidah Wahidah (Universitas Nahdlatul Ulama Lampung, 2015)
Group counseling services in guidance and counseling is one way to help achieve the goals of education. The purpose of this study to determine the relationship of group counseling services and the learning achievement of Islamic religious education in high school Purbolinggo East Lampung. This research is a quantitative, descriptive study of quantitative and correlative shape. The population of the author in this study were students of class XI High School in East Lampung Purbolinggo which consists of 6 classes with a total of 214 with a sample of 32 students. The method used was a questionnaire, interview, observation and documentation. Technical analysis of the data that researchers use a formula of product moment. The results showed that count is greater than table at a significance level of 5% is 0.361 and 1% significance level is 0.463. Or 0.463 <0.603> 0.361. The conclusion of this study is that the authors propose Ha accept that there is a relationship between the counseling group and the learning achievement of Islamic religious education in high school Purbolinggo East Lampung.